Pengaruh Literasi Keuangan, Pendapatan, Ekspektasi Return, dan Fluktuasi Harga Emas Terhadap Minat Berinvestasi Emas di Kalangan Gen Z: Studi Kasus Pada Kota Jakarta Barat - Natasya Prawesti; Randy Kuswanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of financial literacy, income, Return expectations, and gold price fluctuations on interest in investing in gold among Gen Z in West Jakarta City. This research design is quantitative research. The object of this research is Gen Z who lives in West Jakarta. Respondent data collection was carried out by distributing questionnaires in the form of google forms through online media. The assessment in the questionnaire uses a Likert scale. The sampling technique used purposive sampling method. The data obtained were analyzed using multiple linear regression to determine the extent to which each variable affects gold investment interest. This study indicates that financial literacy and gold price fluctuations have a positive and significant effect, while income and Return expectations have a negative and insignificant effect on Gen Z's interest in investing in gold in West Jakarta. This research is expected to be the basis for formulating more effective financial education strategies and investment policies to increase public participation in gold investment.